Firm-level Impact of Regulatory Compliance Costs on Small Business Growth - Francisco, Jamil Paolo; Flaminiano, John Paul; Santamaria, Jose Gerardo; Uel Abad, Joshua (Senate Hall, 2022)
Using firm-level data from a survey conducted in 2019 among a representative sample of small and medium-sized enterprises (SMEs) in the Philippines, we test whether time and monetary costs of regulatory compliance have a negative impact on the incidence of firm growth. We also examine this relationship differentiating between young firms and old firms. We find that spending more time dealing with government regulations decreases the probability of sales revenue and workforce growth among SMEs. The negative effect on the probability of growth was found to be larger for younger firms. Each additional working day spent dealing with government regulations is associated with a 1.34 percentage point lower probability of growth for younger firms compared to a 0.53 percentage point lower probability for older firms. Moreover, incurring additional monetary costs on regulatory compliance decreases the probability of growth among younger SMEs, but not among older ones. Our findings imply that policies aimed at improving the ease of doing business must focus especially on young firms to minimize harmful effects of regulation.
Keywords: compliance cost|growth|regulation|SMEs|small business